The Controlled Synthesis of Carbon Tubes and Rods by Template-Assisted Twin Polymerization. (28th December 2013) - Böttger-Hiller, Falko; Kempe, Patrick; Baumann, Gisela; Hietschold, Michael; Schäfer, Philipp; Zahn, Dietrich R. T.; Petzold, Albrecht; Thurn-Albrecht, Thomas; Spange, Stefan
Abstract : The application of porous carbon is versatile. It is used for high-performance catalyst support, electrode material in batteries, and gas storage. In each of these application fields nanostructuring improves the material properties. Supercapacitors store a high energy density. Exactly adapted carbon structures increase the life of lithium batteries and protect catalysts with increasing reaction rate and selectivity. Most of porous carbon materials have a spherical shape. To the best of our knowledge, there is no procedure to synthesize nanostructured cylindrical porous carbon systematically. Here, template glass fibres and SiO2 -tubes were modified with nanostructured SiO2 /phenolic resin and SiO2 /poly(furfuryl alcohol) layers by surface twin polymerization (TP) of 2, 2′-spirobi[4 H -1, 3, 2-benzodioxasiline] and tetrafurfuryloxysilane. Afterwards the SiO2 /polymer layer on the template is thermally transformed into a defect-free nanostructured SiO2 /carbon layer. After completely removing the SiO2 components microporous carbon tubes or rods are finally achieved. The diameters of the carbon rods and the inner as well as the outer diameter of the carbon tubes are adjustable according to the shape and size of the template. Thus, a huge variety of microporous carbon materials can be easily produced by template-assisted TP.